Analisis Determinasi Kebijakan Dividen Pada Perusahaan LQ45 - Muhammad Nur Adli; Tri Hesti Utaminingtyas; Hera Khairunnisa (Jurnal Akuntansi, Perpajakan dan Auditing, 2024)
The purpose of this study is to test and analyze managerial ownership, profitability, investment opportunity set, and debt to equity ratio to dividend policy. This study uses secondary data sources derived from the company's annual report on companies listed in the LQ45 index on the Indonesia Stock Exchange (IDX) in 2018-2022 using purposive sampling techniques. The analysis technique used is regression analysis of panel data using Econometric Views 13 (EViews) software. The  findings  indicated  that  the  managerial ownership had no bearing on dividend policy, the profitability significantly impacted dvidend policy, the investment opportunity set had no bearing on dividend policy, the debt to equity ratio significantly impacted dividend policy significantly impacted sustainability report disclosure.